Purification and Chitinolytic Characteristics of Chitinases A and B from Serratiamarcescens - Baban, Jamil A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In Serratiamarcescensthe enzymatic chitinolytic machinery of is one of the best that can convert insoluble polysaccharides. This process includes four chitin-active enzymes: ChiA, ChiBand ChiC, an endo-acting non-processivechitinase, , two processivechitinases moving along chitin chains in opposite directions. Serratiamarcescensas a Gram-negative soil bacterium produces these three chitinases, ChiA, ChiB and ChiC which together enable Serratiamarcescens to perfectly degrade the insoluble chitin polymer. The data collected for the pseudotrisaccharideallosamidinshows a comparative inhibition including the cyclic pentapeptideargadin. ChiA, ChiBand ChiC play different roles during chitin degradation was confirmed by the synergistic effects that were observed for certain combinations of ChiA, ChiBand ChiC.
Keywords: Allosamidin; Chitin,CBP21; Isothermal Titration; Calorimetry; Chitinases; E coli; harbouring plasmid